How Can Courts Encourage Constitutional Replacement? - Verdugo, Sergio (SSRN, 2024)
Courts often do not play a significant role in constitutional replacement processes. Observers have identified exceptions and theorized about the courts' possible functions during and after those processes. However, little has been said about the courts' work taking place before replacement processes occur. This essay shows that courts can help establish the conditions for constitutional change by encouraging the demand for such change. They can do that by fostering the perception that the Constitution has become a tool to help one side of the political struggle win over politically salient constitutional conflicts, thus contributing to the polarization among competing political groups. Observers have reported that backlash against the courts is possible. I claim that a backlash against the Constitution itself is also possible. Encouraging the losers of the constitutional conflict to either attack the court or the constitution is possibly an unintended consequence of judges deciding cases in politically consequential ways. The implication is that strategic judges must balance the need to resolve cases in ways they perceive correct with the longterm acceptance of the Constitution. Still, a collective action problem makes this task difficult to achieve. The essay explores these ideas using different examples and expands on how the Chilean Constitutional Court contributed to building opposition against the Constitution before the Constitutional Convention was convened.
Keywords: Constitution making; Constitutional change; Constitutional courts; 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas